The Monoiodoacetate (MIA) Tolerance Test, a New Quantitative Method for the Fibrin Stabilizing Factor (Factor XIII) Assay - Sigg, P (Thrombosis and Haemostasis, 1966)
A new quantitative test for the fibrin stabilizing factor (FSF, factor XIII) determination is described. The test is based on the principle of the reversible inhibition of the FSF action by monoiodoacetate (MIA).The definition of the MIA tolerance is given. The normal range is about 45. The MIA tolerance is studied under various conditions. No FSF free material is necessary for its performance.